Boiling hot! Economy-wide impacts of climate change on Colombian coffee yields - Sayon, Pedro Levy; Otero-Cortés, Andrea; Ceballos-Sierra, Federico; Haddad, Eduardo A. (Springer, 2023)
This chapter quantifies the effects of climate shocks on coffee yields within the ICGE framework. Although macro-results tend to be relatively small, they are very heterogeneous among sectors and regions. Even though the climate shock initially affects areas where coffee is grown, the most positively affected sector in the new equilibrium is coffee processing due to its interindustry chaining in the Colombian. Elevation plays a significant role in this simulation: Lower regions may become unsuitable for coffee, whereas Andean regions will potentially experience a sharp increase in productivity for this crop. The chapter concludes with a discussion of the implications of these results for current producing regions, especially in terms of their labor force.